Clinical Correlates and Prognostic Significance of Lateralized Periodic Discharges in Patients Without Acute or Progressive Brain Injury: A Case–Control Study. Issue 6 (December 2015) - Sainju, Rup K.; Manganas, Louis N.; Gilmore, Emily J.; Petroff, Ognen A.; Rampal, Nishi; Hirsch, Lawrence J.; Gaspard, Nicolas
Abstract : Purpose: Lateralized periodic discharges (LPDs, also known as periodic lateralized epileptiform discharges) in conjunction with acute brain injuries are known to be associated with worse prognosis but little is known about their importance in absence of such acute injuries. We studied the clinical correlates and outcome of patients with LPDs in the absence of acute or progressive brain injury. Methods: This is a case–control study of 74 patients with no acute brain injury undergoing continuous EEG monitoring, half with LPDs and half without, matched for age and etiology of remote brain injury, if any, or history of epilepsy. Results: Lateralized periodic discharges were found in 145/1785 (8.1%) of subjects; 37/145 (26%) had no radiologic evidence of acute or progressive brain injury. Those with LPDs were more likely to have abnormal consciousness (86% vs. 57%; P = 0.005), seizures (70% vs. 24%; P = 0.0002), and functional decline (62% vs. 27%; P = 0.005), and were less likely to be discharged home (24% vs. 62%; P = 0.002). On multivariate analysis, LPDs and status epilepticus were associated with abnormal consciousness ( P = 0.009; odds ratio = 5.2, 95% CI = 1.60–20.00 and P = 0.017; odds ratio = 5.0, 95% CI = 1.4–21.4); and LPDs were independently associated with functional decline ( P = 0.001; odds ratio = 4.8, 95% CI = 1.6–15.4) and lower likelihood of being discharged home ( P = 0.009; odds ratio = 0.2, 95% CI = 0.04–0.6). Conclusions: Despite absence of acute or progressive brain injury, LPDs were independently associated with abnormal consciousness and worse outcome at hospital discharge.